P354 Mold infections in solid organ transplant recipients in indian setting. (20th September 2022) - Enaganthi, Niveditha; Sridhar, Kripa; J, Rajkumar; S, Subramaniam Swaminathan; Verghese, Joy; Reddy, Sreenivas, Selva, Muthukumar, Balaji, Lokeshwari, Mouleeswaran
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Background: Fungi are ubiquitous in nature and the risk of infection rises when a person is immunosuppressed. Prior studies have shown that 70% of all invasive fungal infections in transplant recipients were invasive mold infections (IMI). Mold infections carry a substantial clinical and economic burden in solid organ transplant recipients. Common pathogens include Aspergillus, Zygomycetes, and Fusarium . Objective: To review invasive mold infections in solid organ transplant (SOT) recipients in the last 7 years (2015–2021). It is a retrospective study assessing the risk, clinical features, site of infection, microbiology, management, and outcome. Methods: We retrospectively analyzed the results from 26 patients (2.2%) out of total 1242 (liver 869, kidney 219, lung 91) post-solid organ transplant with proven invasive mold infection extracted from GGHC, Chennai, India. Results: A total of 26 patients post solid organ transplant recipients developed mold infection. In all, 10 patients were diabetic, 8 patients had re-surgery, 3 patients with bile leak, and 5 patients had graft rejection. These risk factors were noted in the group. A total of 10 patients had received multiple transfusions of various products on more than two occasions. A total of 11 patients developed invasive mold infection around 10-30 days post-transplant and Aspergillus was the mold, identified in maximum of 11 people followed by Zygomycosis in 9 patients. In all, 13 patients developed surgical site infection followed by lung lesions in 4 and disseminated in 3 patients. Patients were on oral and intravenous antifungal therapy. A total of 12 patients received amphotericin B overlapping with azole for a brief period followed by oral azole therapy. Anidulafungin was also given as a combination in 5 patients and others received posaconazole or voriconazole. Outcome: A total of 6 patients had good outcomes while 11 patients succumbed to invasive infection post-transplant, 9 patients were unable to trace. Conclusion: Diabetes, re-surgery due to bile leak, any intra-abdominal collection or graft rejection were noted to be risk factors for invasive fungal infection. Aspergillus and Zygomycosis were the frequently isolated molds in this group. It was observed in the group, if the occurrence of mold infection was ˂3 weeks post-transplant, the outcome was worse.